Men Without Fingers, Men Without Toes - Dobson, Kit (Text Matters: A Journal of Literature, Theory and Culture, 2019)
What happens once the rogue rides off into the sunset? This cross-genre essay considers the figure of the rogue’s decline and gradual dismemberment in the face of the pressures of the world. Beginning with the “rogue” digits and other body parts lost by the men who surrounded him in his youth—especially his grandfather—Dobson considers the costs of labour and poverty in rural environments. For him, the rogue is one who falls somehow outside of cultural, social, and political norms— the one who has decided to step outside of the establishment, outside of the corrupt élites and their highfalutin ways. To do so comes at a cost. Turning to the life of writer George Ryga and to the poetry and fiction of Patrick Lane, this essay examines the real, physical, material, and social costs of transgression across multiple works linked to rural environments in Alberta and British Columbia. The essay shows the ways in which very real forms of violence discipline the rogue, pushing the rogue back into submission or out of mind, back into the shadowy past from whence the rogue first came. Resisting nostalgia while evincing sympathy, this essay delves into what is at stake for one who would become a rogue.